2020
DOI: 10.1002/ps.6082
|View full text |Cite
|
Sign up to set email alerts
|

Identification of key genes associated with overwintering in Anoplophora glabripennis larva using gene co‐expression network analysis

Abstract: BACKGROUND Anoplophora glabripennis (Coleoptera: Cerambycidae) is a major quarantine pest in forestry. It is widely distributed throughout many regions such as Asia, Europe, and North America, and has enormous destructive potential for forests. The larvae of A. glabripennis overwinter in a dormant state with strong cold tolerance, and whether the larvae survive winter determines the population density in the following year. However, the molecular mechanisms of this process are not clear. RESULTS RNA sequencing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 64 publications
(67 reference statements)
0
12
0
Order By: Relevance
“…In A. glabripennis larvae, the gene expression level of glycerol kinase increased sharply at the midpoint of the overwintering stage, and then declined at the latter, which corresponded to the change in glycerol content. The findings suggest that glycerol kinase is involved in the synthesis of glycerol, which could help this insect adapt to low temperatures 49 .…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…In A. glabripennis larvae, the gene expression level of glycerol kinase increased sharply at the midpoint of the overwintering stage, and then declined at the latter, which corresponded to the change in glycerol content. The findings suggest that glycerol kinase is involved in the synthesis of glycerol, which could help this insect adapt to low temperatures 49 .…”
Section: Discussionmentioning
confidence: 89%
“…The other pathway converts dihydroxyacetone-3-phosphate to glycerol via GPDH/GK ( S. exigua ) 30 . Identification of key genes associated with overwintering in Anoplophora glabripennis (Motschulsky) larva, a coleopteran species, using gene co-expression network analysis, was demonstrated that, fatty acid desaturase, glycerol phosphate dehydrogenase, glycerol kinase, and trehalose phosphate synthase were among the 15 genes implicated in the control of antifreeze protectants 49 . We studied on GPDH and GK genes expression to investigate the glycerol production pathway.…”
Section: Discussionmentioning
confidence: 99%
“…WGCNA was used to analyze the association between the co‐expressed gene modules. It was also previously used for describing the embryonic development process in Nilaparvata lugens embryos and revealing key genes involved in overwintering in Anoplophora glabripennis larvae (Fan et al ., 2020; Xu et al ., 2021). A gene clustering tree was constructed based on the correlation between the expression levels of genes.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, epigenetic modifications of some genes in the early stages of embryos may be derived from parents. For example, a higher level of DNA methylation appears in the B. mori ovary and enhances the expression of protein synthesis‐related genes (Xu et al ., 2021). A higher level of DNA methylation in the early embryonic stages may also regulate the expression of protein synthesis‐related genes.…”
Section: Discussionmentioning
confidence: 99%
“…A. glabripennis larvae were found to produce cryoprotectants such as glycerol, glucose, and free amino acids during overwintering, leading to improved cold tolerance [ 32 ]. Transcriptome analysis of A. glabripennis larvae at different overwintering stages showed that the expression of heat shock protein, glycerol kinase, aquaporin, and ribosomal protein genes initially increased and then decreased with the changes of ambient temperature [ 33 ]. In total, 47 Hsp genes were identified in the A. glabripennis genome, 13 of which were significantly upregulated during overwintering.…”
Section: Introductionmentioning
confidence: 99%